Locus of Control, Healthy Lifestyle Behavior, and Psychological Well-Being among Student Athletes in Indonesia - Gabriel Gabe Hutapea; Arthur Huwae (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Student athletes face the dual pressures of academic and sporting demands, which make them vulnerable to mental health problems. To be able to improve psychological well-being, it is necessary to have a locus of control from within student athletes, so that they are expected to be able to control themselves to carry out healthy living behaviors, so that psychological well-being can increase. Therefore, this study aims to analyze the relationship between locus of control, healthy living behaviors, and psychological well-being in student athletes in Indonesia. This study used a quantitative approach and multiple correlation analysis design involving 418 participants from various provinces in Indonesia. This study used 3 scales consisting of, IPC LOC (Internality, Powerful Others, and Chance Locus of Control), The Health-Promoting Lifestyle Profile II, and the scale of Psychological Well-Being. The result showed a significant relationship between locus of control with psychological well-being (r = 0,758 and sig. = 0,000), and healthy lifestyle behavior with psychological well-being (r = 0,513 and sig. = 0,000). The results obtained found that locus of control and healthy lifestyle behavior have a relationship with the achievement of psychological well-being of student athletes.